Study of dijet events with large rapidity separation in proton-proton collisions at √s = 2.76 TeV - Tumasyan, Armen; Adam, Wolfgang; Andrejkovic, Janik Walter; Borshch, Vladislav; Ivanchenko, Vladimir; Tcherniaev, Evgueni (Journal of high energy physics)
The cross sections for inclusive and Mueller-Navelet dijet production are measured as a function of the rapidity separation between the jets in proton-proton collisions at root s = 2.76 TeV for jets with transverse momentum p(T) > 35 GeV and rapidity vertical bar y vertical bar < 4.7. Various dijet production cross section ratios are also measured. A veto on additional jets with p(T) > 20 GeV is introduced to improve the sensitivity to the effects of the Balitsky-Fadin-Kuraev-Lipatov (BFKL) evolution. The measurement is compared with the predictions of various Monte Carlo models based on leading-order and next-to-leading-order calculations including the Dokshitzer-Gribov-Lipatov-Altarelli-Parisi leading-logarithm (LL) parton shower as well as the LL BFKL resummation.